Clinical and histological profile of leprosy patients at rural based tertiary care centre in post elimination era - Bindal, Tanupriya; Kalra, Ivreet Kaur; Garg, Monika; Mahindra, Aneet; Nangia, Rattan (Annals of Pathology and Laboratory Medicine, 2018)
Background: Despite India having achieved the national leprosy elimination goal of prevalence rate less than one case per 10000, the disease is still prevalent. Its diverse presentation depending on immune status of host warrants a clinico-histological correlation for diagnosis and start of proper therapy. Aim: The present study was done with the aim to describe the spectrum of clinical and histological profile of leprosy patients especially in doubtful and difficult cases especially where the clinical diagnosis is not sufficient and, then, to correlate clinical and histological profile. Methods: This study is a hospital based prospective study conducted on sixty newly diagnosed cases of leprosy. Skin biopsy was taken in each case and processed routinely. All the cases were stained with hematoxylin and eosin and modified Ziehl-Neelsen stain. Ridley-Jopling classification was used for diagnosis and typing of cases. Results: In the present study consisting of 60 newly diagnosed leprosy patients, majority of the cases i.e. 18 (30%) were in age group of 21-30 years with male: female ratio of 1.6:1. The most common type of skin lesion was plaque (50%), followed by hypo-pigmented macule (33.3%). The clinico-pathological concordance was maximum in Tuberculoid (TT) (100%) followed by Lepromatous (LL) (80%), Borderline lepromatous (BL) (72.7%), Borderline tuberculoid (BT) (50%) and Mid-borderline (BB) (33.3%). Conclusion: The overall clinicopathological concordance in present study is good (66.7%). Thus, the correlation of clinical and histological features along with bacillary index is far more useful for accurate typing and therapy in leprosy patients. DOI:10.21276/APALM.1680